1961
DOI: 10.1007/bf01440487
|View full text |Cite
|
Sign up to set email alerts
|

�ber das Verhalten der Glutamat-Oxalacetat-Transaminase, Glutamat-Pyruvat-Transaminase, Sorbit-Dehydrogenase und Cholinesterase im Serum nach Herzoperationen

Abstract: Die Tatsache, dal~ sich die bisher untersuchten Serumenzyme bei verschiedenar~igen akuten Ereignissen gleichsinnig ver/~ndern, veranlaltte HAvss u. Mitarb2, ~0, das Verhalten der Enzyme als Teilreaktion einer allgemeinen vegetativen Umschaltung zn betraehten. Demgegenfiber sind andere Autoren der Meinung, dab die im Strum nachweisbaren Aktivit~tssteigernngen dnrch den Anstritt der Enzyme aus den jeweils gesch~digten Organbezirken zustande kommen s, 7, 25Bei Operationen am offenen tterzen treffen mehrere Faktor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1963
1963
1974
1974

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…I n 1957, Crafoord et al (7) and Schlief and Kamm (38) reported the first observations on the serum enzyme alterations after cardiovascular operations. Thereafter, this subject has been dealt with in several studies (4, 6,9,17,27,33,35,39,41,46). Glutamic-oxalacetic transaminase (GOT) activity has been studied most extensively.…”
mentioning
confidence: 99%
“…I n 1957, Crafoord et al (7) and Schlief and Kamm (38) reported the first observations on the serum enzyme alterations after cardiovascular operations. Thereafter, this subject has been dealt with in several studies (4, 6,9,17,27,33,35,39,41,46). Glutamic-oxalacetic transaminase (GOT) activity has been studied most extensively.…”
mentioning
confidence: 99%